Dampak Implementasi Penyatuan Bagian IT Menjadi Satu Divisi Menggunakan Strategi Change Management di PT XYZ - Purnomo, Lorio; Kurniawan, Anton; Basuki, Carola; Pratama, Anggha Dipa; Paramadita, Siti (APPS Publications, 2023)
ABSTRACT In the era of Industry 4.0, many companies demand to determine a Change Management Strategy in order to maximize capacities and efficiency. Currently, PT XYZ sees existing problems in the IT division, which are not meeting demands as expected and slowing down the whole organization’s development. In accordance with these problems, Project Monitoring methods are proposed to be applied in PT XYZ’s organizational structure as a result of the Change Management Strategy. A Change Management Strategy will be implemented in the IT division using the proposed methods; Kotter’s Model and 7-S Framework followed by the development of a project monitoring application called Dashboard Monitoring. In accordance, with Kotter’s Model’s approach, the creation of two new positions is highly recommended inside the IT division to support its effectiveness. These positions are Project Management Officers and Business Analysts. These two positions are expected to focus more on the process of developing new applications and/or systems. Thus, the 7-S Framework implementation will be supporting the change of Shared & Value from the change in the organizational structure of PT XYZ with the objective of simplifying the process of analyzing and decision-making at the managerial level, especially in terms of deciding to create an application. Furthermore, a Dashboard Monitoring application has been implemented in PT XYZ, resulting in improvements in lead time and productivity throughout multiple IT projects. Objective – Developments in the era of Industry 4.0 make all companies adapt towards digitalization, to determine Change Management Strategies to maximize capacity and efficiency. PT XYZ sees problems in the IT division, where the IT Division cannot meet the demands as expected. Thus, resulting in delays in the development of the organization. Obstacles in processing so many requests in making applications between divisions in the company, developing a product application system is the biggest obstacle faced by PT XYZ. Methodology – The author uses the following Research Methodology; (1) understand the identification of existing problems based on the author's observations and communication with PT XYZ; (2) study the organizational structure: (3) Literature Review; (4) Interviews and observations at PT XYZ. The first stage is interviews with all Vice Presidents from all divisions at PT. XYZ. The second stage is an interview by asking the Chief Executive Officer of the company regarding information related to changes in the IT Division. ; (5) Kotter Framework and 7-S approaches, all of which start with analyzing with Dynamic Capability Theory; (6) Provide recommendations, propose to create a new IT division, then analyze the new organizational structure using the 7-S Framework and produce proposed new values. Findings – The author got information from PT XYZ Top Management, where from the results of this interview a Change Management Strategy is proposed to be implemented in the organizational structure of PT XYZ. The Change Management Strategy will be implemented in the IT division using the proposed method, namely the Kotter Model and the 7-S Framework, which were previously analyzed using the Dynamic Capability approach. Then followed by the development of a project monitoring application called Dashboard Monitoring. Novelty – The author implementing the 7-S Framework to support Shared & Value changes from changes in PT XYZ's organizational structure. Next implement the Kotter Model Strategy which explains 8 Strategies to produce recommendations for changes to PT XYZ's organizational structure, by adding the positions of PMO (Project Management Officer) and BA (Business Analyst). In addition, the Dashboard Monitoring application was also implemented at PT XYZ, resulting in increased lead time and productivity in various IT projects.